Multilayered models for determining the Young's modulus of thin films by means of Impulse Excitation Technique. (October 2019) - Zgheib, Elia; Alhussein, Akram; Slim, Mohamed Fares; Khalil, Khaled; François, Manuel
Highlights: Two analytical models were developed to determine the coatings Young's moduli. Numerical model was developed to validate the proposed models. Ti and Nb thin films were deposited by pulsed-DC magnetron sputtering. Young's modulus was measured using Static (NI) and Dynamic (IET) techniques. The film morphology and microstructure influence its elasticity behavior. Good agreement has been noticed between the different approaches. Abstract: This work presents a methodology to determine the Young's modulus of an individual coating in a multilayered system by means of the Impulse Excitation Technique (IET). In this technique, the composite beam is excited by an impulse and the frequencies of the first four bending modes are extracted. They are used in a one-dimensional model to obtain the Young's modulus of the coating. Based on two different theories: the Flexural Rigidity of a Composite Beam (FRCB) and the Classical Laminated Beam Theory (CLBT), different models proposed in the literature for bilayer beams have been extended to describe a beam composed of N dissimilar layers. Moreover, an enhanced model was developed based on the laminated theory. It takes into account the shift of the neutral axis after each deposited film, which makes it applicable for any film thickness. The reliability of the proposed model is investigated by comparing its predicted frequency to those of existing models for bilayers. It is also compared to finite element analysis of beams composed of two and three dissimilar layers. A metrological study was performed to quantify the most influencing factors on the global uncertainty. The methodology was applied to beams composed of three layers ( N = 3) with titanium and niobium thin films deposited by DC magnetron sputtering. The most accurate models are applied to obtain the Young's modulus of Ti and Nb films in the Ti/Nb/(AISI 316 or Glass) multilayer beam. The films microstructure and morphology were analyzed by X-ray diffraction and scanning electron microscopy.